Exploration of The Daily Dietary Patterns of Rice Farmers in Rambigundam Village Rambipuji District Jember Regency - Intan Ayu Nur Aini; Ardiana, Anisah; Purwandari, Retno; Asmaningrum, Nurfika; Kurniawati, Yulia (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Dietary patterns is the most important behavior that affects a person's nutritional state. The dietary patterns consists of three components, which include the types of food, eating schedules, and meal portions. Objectives: This study aimed to analyzed the daily dietary patterns of rice farmers in Rambigundam Village, Rambipuji District, Jember Regency. Methods: This research is a quantitative research used a descriptive research design and the sampling technique used is purposive sampling. The sample in this research were rice farmers totaling 205 people who fit the inclusion criteria. Data were collected used the Daily Dietary Patterns Questionnaire which consisted of 20 statement items that had 4 answer options, namely never, sometimes, often, and always, each with a different score. Data analysis in this research used univariate analysis. Results: The results of this research showed that the daily dietary patterns of rice farmers in Rambigundam Village are varied, some are moderate (36,1%), good (35,6%), and poor (8,3%). Discussion: Differences in dietary patterns among farmers can be influenced by the amount of income and education they have. Conclusions: Nurses as educators can provided information regarding good dietary patterns so that it is hoped that farmers can improve their dietary patterns which included food variety, eating schedules, and meal portions that can be fulfilled properly, in order to achieve optimal health status. Apart from that, farmers are also encouraged to actively seek information related to supporting a good diet, considering that working as a farmer is hard work and drains energy.